1990
DOI: 10.1007/bf00975149
|View full text |Cite
|
Sign up to set email alerts
|

Sleep of chronic post-traumatic patients

Abstract: The purpose of the present study was to investigate the sleep of people diagnosed as suffering from chronic Post-Traumatic Stress Dkorder (PTSD). The sleep of seven chronic post-traumatic patients with no known physical injuries was compared with that of seven matched control subjects. The post-traumatic patients had poorer sleep: decreased sleep efficiency, increase in number of awakenings, and decreased SWS, as well as longer REM latency. It was also found that their complaints correlated with relevant sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 6 publications
4
25
1
6
Order By: Relevance
“…In PTSD patients the most consistent polysomnography findings are difficulty in sleep initiation and maintenance, including poor sleep efficiency, [3][4][5][6][7][8][9] decreased total sleep time (TST), 3,4 increased sleep latency, 4,5 and increased number of awakenings. [3][4][5] These findings, however, were not found in some other studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In PTSD patients the most consistent polysomnography findings are difficulty in sleep initiation and maintenance, including poor sleep efficiency, [3][4][5][6][7][8][9] decreased total sleep time (TST), 3,4 increased sleep latency, 4,5 and increased number of awakenings. [3][4][5] These findings, however, were not found in some other studies.…”
mentioning
confidence: 99%
“…Some studies have reported decreased SWS. 5,6,9,16 *Correspondence: Sinan Yetkin, MD, Department of Psychiatry, Diyarbakır Military Hospital, 21300 Diyarbakır, Turkey. Email: snnyetkin@gmail.com Again, numerous other studies did not find any differences in SWS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All of them included patients with depressive disorders, which are associated with an increase of REM density in REM sleep [54]. Evidence of REM fragmentation has been reported several times [22, 27, 37]. However, 7 studies did not find elevated REM interruptions [24, 25, 30, 31, 33, 38, 43].…”
Section: Ptsd and Sleepmentioning
confidence: 99%
“…In explaining the high occurrence of posttraumatic anxiety dreams and reports of the occurrence of those dreams in NREM sleep (see below) it is important to rely on empirical evidence regarding the characteristics of REM sleep in PTSD patients. Table 1 summarizes REM sleep parameters of 26 polysomnographic studies [22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51] on PTSD samples.…”
Section: Ptsd and Sleepmentioning
confidence: 99%